Tribological behaviour of reactive and co-sputtered W-S-C coatings - Evaristo,M. (2006)
W-C-S films were deposited either by a reactive process in an Ar+CH4 atmosphere or by co-sputtering WS2 and C targets. The films were characterized concerning their chemical composition and mechanical properties. The results showed that the films, in both systems, have similar properties. Co-sputtered films are amorphous, whereas in the reactive process a gradual l oss of cristallinity is observed with the increase of C content in the films. The hardness and the adhesion are similar for both systems. The increase of C alloying to the films led to the improvement of both their hardness and adhesion. The tribological performance of the coatings was tested by ball-on-disk. The films deposited by co-sputtering present better results than the reactive deposited ones. With the increase of C content in these coatings an increase of the wear resistance is observed, reaching in the best case a wear coefficient of 3.1×10-16 m³/N×m. In the films deposited by reactive process, low wear coefficients can also be reached but no regular trend with increasing C contents can be observed.